2015
DOI: 10.5424/sjar/2015132-6567
|View full text |Cite
|
Sign up to set email alerts
|

Description of the airflow produced by an air-assisted sprayer during pesticide applications to citrus

Abstract: Atmospheric drift of plant protection products is considered a major source of air pollution during pesticide applications. Citrus protection against pests and diseases usually requires application of these products using air-blast sprayers. Many authors have emphasized the influence of vegetation on the risk of spray drift. The aim of this work was to describe in detail how the airflow from an air-blast sprayer behaves when it reaches citrus trees and, in particular, the effect that the tree canopy has on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…Likewise, in bush/tree crop spray applications, the air flow of the sprayer fan plays a crucial role in ensuring the biological efficacy of treatments and reducing the drift risk . The parameters of air jet (air flow rate [AFR] and velocity), related to the construction technique of fan type, together with sprayer forward speed are main factors influencing the quality of the treatments and the spray off‐target losses, significantly contributing to environmental pollution…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in bush/tree crop spray applications, the air flow of the sprayer fan plays a crucial role in ensuring the biological efficacy of treatments and reducing the drift risk . The parameters of air jet (air flow rate [AFR] and velocity), related to the construction technique of fan type, together with sprayer forward speed are main factors influencing the quality of the treatments and the spray off‐target losses, significantly contributing to environmental pollution…”
Section: Introductionmentioning
confidence: 99%
“…In agrochemical applications on orchards and vineyards, the idea of producing droplets by using nozzles and transporting them to vegetation, by using an air jet generated by a fan, is now the generally accepted method. Some studies [1][2][3][4][5][6] have demonstrated that stream speed strongly influences the effectiveness of spray treatment. If the speed is too low, the distribution of chemicals on vegetation tends to be non-uniform.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, if the speed is too high, the leaves align with the air stream, and much of the spray is not captured by the vegetation. Spray drift increases with velocity until approximately 50% of the spray does not land on the vegetation [3,4] and, consequently, causes both economic loss and environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…
ElsevierSalcedo Cidoncha, R.; Granell Ruiz, R.; Palau-Salvador, G.; Vallet, A.; Garcerá, C.; Chueca, P.; Moltó, E. (2015). Design proposes and validates a two dimensional CFD model to be applied in citrus tree 19
…”
mentioning
confidence: 99%
“…Inside the domain, three regions corresponding to canopies were defined, each one 227 representing the cross-section of a row of trees. Based on our previous experience 228 (Salcedo et al, 2013(Salcedo et al, , 2015, it was decided to consider the region nearest to the air inlet 229 to be a solid medium with homogeneous characteristics, while the other two regions 230 were modelled as a porous medium. Even considering the first region as a solid 231 medium, its dimensions should be smaller than those of the true trees because otherwise 232 the airflow would take a very vertical direction with extremely quick velocities due to 233 the Venturi effect.…”
mentioning
confidence: 99%